Metaphors we live by in Brazil: anthropophagic notes on classic and contemporary approaches to metaphor in the Brazilian scientific-academic context / Metáforas da Vida Cotidiana no Brasil: notas antropofágicas sobre abordagens clássicas e contemporâneas da metáfora no contexto acadêmico-científico brasileiro (Revista de Estudos da Linguagem, 2020)
.